Pengaruh Kemudahan Electronic Money (E-Money) Terhadap Perilaku Konsumtif Mahasiswa Uinsi Samarinda Pada Masa Pandemi Covid-19 - Putra Aditya, Muhammad Arya; Iswadi, Muhammad; Hamidy, Anwaril (Borneo Islamic Finance and Economics Journal, 2023)
This research aims to 1). Knowing the effect of electronic money (e-money) on the consumptive behavior of UINSI Samarinda students during the Covid-19 pandemic, 2). To find out how much influence the convenience of electronic money (e-money) has on the consumptive behavior of UINSI Samarinda students during the Covid-19 pandemic. The type of research used is associative descriptive quantitative research.This study used primary data from a questionnaire filled out by UINSI Samarinda students.The population in this study were UINSI Samarinda students, totaling 6,650 students. The sample in this study was determined using the Slovin formula as many as 100 people using a purposive sampling technique. The analysis technique used is simple linear regression analysis with the SPSS 28 program. Based on the results of the calculation of the t test, the e-money convenience variable has a significant effect on the consumptive behavior of UINSI Samarinda students. The convenience of e-money has a positive effect on consumptive behavior. There is a 3% effect between the ease of e-money on consumptive behavior, and 97% from other variables. Keywords: E-money Ease, Consumptive Behavior